Metal magnetic powder with multiple synergistic protective films on surface and preparation method of metal magnetic powder
By phosphating and chemical oxidizing the Sm2Fe17Nx magnetic powder, a multiple coordinated protective film was formed and heat treatment was carried out in an oxygen partial furnace, the problem of easy oxidation and combustion of magnetic powder at high temperatures was solved, and its antioxidant performance and service life were significantly improved.
Patent Information
- Application Number
- CN202510361533.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-26
AI Technical Summary
Sm2Fe17Nx magnetic powder is easy to oxidize and burn in the air, and the prior art is difficult to effectively improve its high-temperature oxidation resistance.
Through phosphating treatment and chemical oxidation treatment under the protection of an inert atmosphere, multiple coordinated protective films are formed, including phosphating films and metal oxide films, and heat treatment in a low-oxygen environment is carried out in an oxygen partial furnace to form a uniform and dense protective film.
It significantly improves the antioxidant performance of metal magnetic powder at high temperatures, extends its service life at high temperatures, and avoids the problem of degradation of permanent magnet performance.
Smart Images

Figure CN119870461A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal magnetic powder preparation and surface modification, and in particular relates to metal magnetic powder with multiple coordinated protective films on the surface and a preparation method thereof. Background Art
[0002] Sm2Fe 17 N x It is a new type of rare earth permanent magnet material developed in recent years. Compared with NdFeB permanent magnet, this type of magnet has similar magnetic properties, and the theoretical maximum magnetic energy product is equivalent to that of NdFeB, and its theoretical value can reach 480KJ / m 3 At the same time, this type of magnet has better temperature and chemical stability. Its Curie temperature is higher than 750K (477℃), which is nearly 160℃ higher than NdFeB (590K or 317℃). It has excellent intrinsic magnetic properties and a large anisotropy field.
[0003] However, this fine magnetic powder has a high surface activity and is very easy to oxidize directly in the air, and it will burn at a slightly higher temperature. Therefore, it is necessary to coat the magnetic powder to improve its oxidation resistance. The coating of Sm-Co permanent magnet material is mainly used to improve the high-temperature oxidation resistance of the magnet. The basic principle is to block or reduce the diffusion of oxygen in the magnet. For example, a layer of metal (Al, Cu, Ni, Cr, Mo and W, etc.) is plated on the surface of the magnet. Experiments have found that a uniform coating with sufficient thickness (not less than 10μm) can provide effective protection for the magnet. Professor Kenichi Machida of Osaka University in Japan (Joint Research Center for Advanced Science and Technology) has developed a technology for surface treatment of magnetic powder by zinc plating and organic silicon compounds to improve the oxidation resistance of anisotropic SmFeN magnetic powder. After treatment, not only the oxidation resistance is improved, but also the powder particles are tightly combined with the resin, and the particles are easy to rotate during alignment. Zhang Dongtao et al. used silane coupling agent KH550 to coat Sm2Fe 17 N x The permanent magnet powder was surface coated, and the oxidation behavior of the magnetic powders in different coating states below 300°C and the change of their magnetic properties were studied. The results showed that the coupling agent was adsorbed on the surface of the magnetic powder in the form of chemical bonds, forming a mesh film, which effectively prevented the contact between the magnetic powder and the oxygen in the environment, thereby improving the oxidation resistance of the magnetic powder at high temperatures.
[0004] Oxidation and corrosion protection of rare earth permanent magnet materials is very important. With the expansion of its application fields, the increasingly harsh service environment and the improvement of user requirements, higher requirements are put forward for oxidation and corrosion protection technology. In view of specific application requirements, it is necessary to develop new protective coatings and their preparation technologies that are effective, environmentally friendly and low-cost. Summary of the invention
[0005] The purpose of the present invention is to address the deficiencies of the prior art and to propose a metal magnetic powder having multiple synergistic protective films on the surface and a method for preparing the same. The surface of the metal magnetic powder has multiple synergistic protective films such as a phosphating film and a metal oxide film. The method for preparing the multiple synergistic protective films is that the metal magnetic powder is first subjected to a phosphating treatment, and then subjected to a chemical oxidation treatment using an oxidant, and finally subjected to a heat treatment in a low-oxygen environment in an oxygen partial pressure furnace, and finally a uniform, dense, and quality-stable multiple synergistic protective film containing a phosphating film and an oxide film is formed on the surface of the powder. Further improve the antioxidant properties of metal powders under high-temperature service. In summary, it is urgent to propose a method for forming a uniform and dense protective film on the surface of a metal powder through synergistic treatment of phosphating and chemical oxidation to improve the antioxidant properties of the powder under high-temperature service.
[0006] The method of the present invention adopts the following technical scheme: In a first aspect, the present invention provides a method for preparing a metal magnetic powder having multiple synergistic protective films on its surface, comprising: Under the protection of an inert atmosphere, the metal magnetic powder is placed in an organic solution containing concentrated phosphoric acid and stirred to obtain a surface-phosphorized metal magnetic powder; Under the protection of an inert atmosphere, the metal magnetic powder with phosphating on the surface is placed in an alkaline solution containing an oxidant, fully stirred at 25-80°C, and allowed to stand for reaction to obtain the metal magnetic powder after chemical oxidation treatment; Under the protection of an inert atmosphere, the metal magnetic powder after chemical oxidation treatment is cleaned and dried to obtain dry metal magnetic powder after oxidation treatment; The dried oxidized metal magnetic powder is placed in an oxygen partial pressure furnace for heat treatment, so that a layer of uniform and dense multi-layer protective film that is well bonded with the matrix is formed on the surface of the metal magnetic powder.
[0007] Preferably, the metal magnetic powder includes one of samarium iron nitrogen magnetic powder, neodymium iron boron magnetic powder, neodymium iron nitrogen magnetic powder, samarium cobalt magnetic powder, samarium iron cobalt magnetic powder and iron nitrogen compound magnetic powder, or a composite thereof.
[0008] Preferably, the oxidant includes one of sodium nitrate, sodium nitrite, hydrogen peroxide, potassium dichromate and potassium permanganate. More preferably, the oxidant is sodium dichromate, and its content is 0.5%.
[0009] Preferably, the solute in the organic solution containing concentrated phosphoric acid is concentrated phosphoric acid with a mass content greater than 80%.
[0010] Preferably, the inert atmosphere comprises one or both of argon and helium.
[0011] Preferably, the phosphoric acid content in the organic solution containing concentrated phosphoric acid is 0.5%-10% of the mass content of the magnetic powder.
[0012] Preferably, the pH of the alkaline solution containing the oxidant is greater than 8, and the oxidant content is 0.1%-1.0% of the mass content of the magnetic powder, more preferably 0.1%-0.5%.
[0013] Preferably, a mixed gas of nitrogen and air or a mixed gas of nitrogen and pure oxygen is introduced into the oxygen partial pressure furnace, and the flow rate of air or pure oxygen is controlled so that the oxygen content in the furnace is 1-15 vol.%. The temperature of the oxygen partial pressure furnace is controlled at 150-250°C, the heating and cooling rates are 2-4°C / min, and the holding time is 30min-2h.
[0014] The solvent of the acid solution is an organic solvent.
[0015] In a second aspect, the present invention provides a metal magnetic powder having multiple synergistic protective films on the surface, which is prepared by the above method.
[0016] Compared with the prior art, the beneficial effects of the present invention are at least: The metal magnetic powder of the present invention is protected by the phosphating film and the metal oxide film, which avoids the problem of loose single-layer film, can effectively isolate the contact between the powder and the air, ensures high-temperature oxidation resistance, and thus improves the coercive force of the metal magnetic powder at high temperature.
[0017] After the phosphating film and the metal oxide film are heat treated in a high temperature furnace under controlled oxygen partial pressure, the heat treatment can not only achieve the dehydration and drying of the chemical phosphating film molecules to ensure the bonding force between the synergistic film and the metal powder, but also micro-oxidize the powder surface at high temperature under trace oxygen to compensate for the formation of an oxide protective film again at the loose part of the synergistic film. At the same time, the high temperature treatment of the powder in advance can avoid the permanent magnetic properties of the metal magnetic powder from decreasing when it is used in an environment below 300°C, making it possible for the metal magnetic powder to be used at higher temperatures, and broadening the applicable market for the metal magnetic powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Schematic diagram of the oxygen partial pressure tube furnace device for heat treatment of metal magnetic powder.
[0019] Figure 2The TEM images and EDS spectra of samarium iron nitrogen magnetic powder particles prepared by multiple synergistic surface treatments in Example 1 and Control Group 1, wherein the elements are Fe, Sm, O, and P, respectively. Among them, (A-1) is the morphology of the magnetic powder particles in Example 1, (A-2) is the iron element distribution diagram of the magnetic powder particles in Example 1, (A-3) is the samarium element distribution diagram of the magnetic powder particles in Example 1, (A-4) is the oxygen element distribution diagram of the magnetic powder particles in Example 1, (B-1) is the morphology of the magnetic powder particles in Control Group 1, (B-2) is the iron element distribution diagram of the magnetic powder particles in Control Group 1, (B-3) is the samarium element distribution diagram of the magnetic powder particles in Control Group 1, (B-4) is the oxygen element distribution diagram of the magnetic powder particles in Control Group 1, (C) is the morphology of the magnetic powder in Example 1, and (D) is the phosphorus element distribution diagram of the magnetic powder in Example 1.
[0020] Figure 3 It is a schematic diagram of the effect of the entire experimental process. The product of the multiple synergistic surface treatment is a multiple synergistic protective film on the surface of the SmFeN magnetic powder particles.
[0021] Figure 4 The flowchart of the whole experiment. DETAILED DESCRIPTION
[0022] As mentioned above, in view of the shortcomings of the prior art, the inventor of this case proposed the technical solution of the present invention after long-term research and extensive practice, the main basis of which at least includes: The present invention firstly phosphates the metal magnetic powder (taking samarium iron nitrogen metal magnetic powder as an example), then uses an oxidant to perform chemical oxidation treatment, and finally performs heat treatment in an oxygen partial pressure furnace in a low oxygen environment, so that the surface of the samarium iron nitrogen magnetic powder finally obtains a multiple synergistic protective film containing both a phosphating film and an oxide film. Due to the formation of the protective film on the surface of the metal magnetic powder, the permanent magnetic properties of the metal magnetic powder at room temperature are greatly improved, the effect of the metal magnetic powder in resisting the decline of the permanent magnetic properties below 300°C and the oxidation resistance at high temperature are improved, the possibility of the metal magnetic powder serving at higher temperatures is realized, and the applicable market of the metal magnetic powder is broadened.
[0023] The present invention provides a method for preparing a metal magnetic powder having multiple synergistic protective films on the surface, such as Figure 4 include: Step 1: Under the protection of an inert atmosphere, place the metal magnetic powder in an organic solution containing concentrated phosphoric acid and stir to obtain a surface-phosphorized metal magnetic powder. Figure 3 .
[0024] In one embodiment, the phosphoric acid content in the organic solution containing concentrated phosphoric acid is 0.5%-10% of the mass content of the magnetic powder, and the stirring treatment time is 10 min-30 min.
[0025] Step 2: Under the protection of an inert atmosphere, place the surface phosphated metal magnetic powder in an alkaline solution containing an oxidant, stir it thoroughly at 25-80°C, and let it stand for reaction to obtain the metal magnetic powder after chemical oxidation treatment. Figure 3 .
[0026] In one embodiment, the oxidant content in the alkaline solution containing the oxidant is 0.1%-1.0% of the mass content of the magnetic powder, the stirring treatment time is 20min-40min, and the standing time is 40min-60min.
[0027] Step 3: Under the protection of an inert atmosphere, the metal magnetic powder after chemical oxidation treatment is cleaned and dried to obtain dry metal magnetic powder after oxidation treatment; For example, the solution for cleaning the metal magnetic powder may be washed with deionized water until it is colorless and transparent, and then the metal magnetic powder is washed twice with an ethanol solution and a normal hexane solution, respectively. The cleaned metal magnetic powder is placed in a glove box with inert atmosphere protection, and dried naturally at room temperature, and finally the dry metal magnetic powder treated with the alkaline pro-oxidant is obtained.
[0028] Step 4: Place the obtained metal magnetic powder Figure 1 Heat treatment is carried out in an oxygen partial pressure furnace, so that a uniform and dense multi-layer protective film that is well bonded to the matrix is formed on the surface of the metal magnetic powder.
[0029] Heat treatment can not only dehydrate and dry the chemical phosphating film molecules, ensuring the bonding force between the synergistic film and the metal powder, but also micro-oxidize the powder surface under a trace of oxygen and high temperature to compensate for the formation of an oxide protective film again at the loose part of the synergistic film. At the same time, the high-temperature treatment of the powder in advance can prevent the permanent magnetic properties of the metal magnetic powder from decreasing when it is used in an environment below 300°C.
[0030] In one embodiment, the metal magnetic powder mentioned in step 1 includes one of samarium iron nitrogen magnetic powder, neodymium iron boron magnetic powder, neodymium iron nitrogen magnetic powder, samarium cobalt magnetic powder, samarium iron cobalt magnetic powder and iron nitrogen compound magnetic powder, or a composite thereof.
[0031] In one embodiment, the solute of the organic solution containing concentrated phosphoric acid mentioned in step 1 is concentrated phosphoric acid with a mass content greater than 80%.
[0032] The acid solution in this embodiment can be a mixture of concentrated phosphoric acid and an organic solvent. Because the metal magnetic powder particles are small and highly active, they are prone to chemical corrosion in aqueous solvents to generate loose products that affect the antioxidant effect. Therefore, the concentrated phosphoric acid used in the phosphoric acid solution has a concentration of more than 80%, and an organic solvent such as anhydrous ethanol, isopropanol or n-hexane is used as the solvent, and water cannot be added.
[0033] In one embodiment, the pH of the alkaline solution containing the oxidant mentioned in step 2 is greater than 8, the alkaline solution can reduce the corrosion problem of the magnetic powder in the aqueous solution, and the oxidant can cause the magnetic powder to undergo an oxidation reaction, wherein the oxidant includes one of sodium nitrate, sodium nitrite, hydrogen peroxide, potassium dichromate and potassium permanganate.
[0034] The oxidant in this embodiment is preferably sodium nitrite. When preparing the solution of the oxidant sodium nitrite, deionized water is finally selected as the solvent because sodium nitrite is slightly soluble in organic solvents such as ethanol. Since metal magnetic powder has a high surface activity, it is very easy to oxidize in the air and even burn in the air, and since sodium nitrite has a strong pro-oxidation property, it may further lead to oxidation and combustion of the metal powder. Therefore, the content of sodium nitrite in the solution should be controlled in a relatively low range, and finally a sodium nitrite content of 0.1%-1.0% of the mass content of the magnetic powder is selected, preferably 0.5%.
[0035] The chemical oxidation treatment of the metal magnetic powder surface is carried out in a pure inert atmosphere vacuum glove box to prevent the highly surface active metal magnetic powder from being oxidized or even burned in the air. The metal magnetic powder is placed in a reagent in which sodium nitrite is completely dissolved, stirred thoroughly and left to stand for a sufficient time to ensure that the surface of the magnetic powder can be more evenly and fully contacted with the reagent, thereby ensuring the uniformity and consistency of the chemical reaction.
[0036] In one embodiment, the carrier gas in steps one, two and three is a pure inert gas, wherein the inert gas includes one or both of argon and helium; so that the oxygen content in the vacuum glove box is less than 5 PPm and the water content is less than 0.1 PPm.
[0037] In one embodiment, the cleaning treatment of the metal powder mentioned in step three is to use three solvents (deionized water, ethanol, and n-hexane) to clean the metal magnetic powder after chemical oxidation treatment. After the surface of the metal magnetic powder is evenly and fully treated, the sodium nitrite remaining on the surface of the metal magnetic powder should be fully cleaned with deionized water, and then the small amount of sodium nitrite and water remaining on the surface of the metal magnetic powder should be further cleaned with ethanol, so that the metal powder is fully cleaned to avoid the residue of oxidant and water solvent, which affects the next step of heat treatment experiment. Finally, the metal magnetic powder is cleaned with n-hexane solution because the n-hexane solution contains almost no oxygen, which can effectively avoid the influence of oxygen element on the vacuum environment and the oxidation of the metal magnetic powder surface in the next step of vacuum drying.
[0038] In one embodiment, the heat treatment of the surface of the metal magnetic powder after drying mentioned in step 4 is to form a uniform and dense oxide film on the surface of the metal magnetic powder. In order to avoid drying at a certain temperature in an oven, the metal magnetic powder is oxidized under the influence of high temperature, humidity and air environment, and finally choose to dry naturally in a vacuum drying environment. The dried metal powder is placed in a crucible and placed in an oxygen partial pressure tube furnace. In theory, if the wet powder is placed in a tube furnace for heat treatment, it will further promote the oxidation of the metal magnetic powder and even cause the oxidation of the metal magnetic powder matrix. Therefore, the metal magnetic powder must be fully dried before the experiment. The metal magnetic powder is heat treated in an oxygen partial pressure tube furnace, in which air or a mixture of pure oxygen and nitrogen is used as the reaction atmosphere, and the oxygen content in the furnace is controlled to be 1-15 vol.%, and the oxygen partial pressure furnace is controlled at 150-250°C, and the insulation time is 30min-2h. A uniform and dense oxide film on the surface of the metal magnetic powder is obtained. The oxidation effect is mainly related to the oxygen content, oxidation temperature and oxidation time. If the oxidation time is too long, the oxygen content and oxidation temperature are too high, it will theoretically lead to serious oxidation of metal magnetic powder, and even the metal powder matrix will be oxidized. High temperature will even cause small-size powder to be decomposed, and finally lead to the complete loss of various properties of metal magnetic powder. If the oxidation time is too short, the oxygen content and oxidation temperature are too low, it will theoretically lead to the oxide film on the surface of metal magnetic powder not being dense enough, loose and porous, and the oxidation resistance will be seriously reduced. Even in the manufacturing process, the oxide film is more likely to fall off, and a good antioxidant effect cannot be achieved. In the heat treatment process of metal magnetic powder, the oxygen content in the furnace should be controlled at a certain value, and the temperature should be slowly increased and decreased at a rate of 2-4℃ / min. In theory, the slow rise and fall of temperature can make the reaction on the surface of metal magnetic powder slow and uniform, which is conducive to the uniform and dense oxide film formed on the surface of metal magnetic powder.
[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0040] The present invention is further described below in conjunction with specific embodiments, but the methods and technical parameters involved in the scheme should not be understood as limiting the present invention. Example 1
[0041] Step 1, under the protection of an inert atmosphere (which can be one or both of argon or helium), dissolve phosphoric acid (concentration of 85%) with a content of 1% by mass of the magnetic powder in anhydrous ethanol and stir and dissolve to form a 1wt.% phosphoric acid phosphating solution; place the metal magnetic powder in the 1wt.% phosphoric acid phosphating solution and stir to obtain a surface-phosphated metal magnetic powder; Step 2: Under the protection of an inert atmosphere, place a NaNO2 solid with a mass content of 0.5% of the magnetic powder in a small amount of deionized water, and adjust the solution pH to 9 with NaOH, stir thoroughly, and form a 0.5% NaNO2 oxidizing alkaline solution; place the surface phosphated metal magnetic powder in a 0.5% NaNO2 oxidizing alkaline solution at 25°C, stir thoroughly, and let stand to react to obtain the metal magnetic powder after chemical oxidation treatment. Then, still under the protection of an inert atmosphere, first wash the solution for cleaning the metal magnetic powder with deionized water until it is colorless and transparent, and then wash the metal magnetic powder twice with an ethanol solution and a n-hexane solution respectively. Place the cleaned metal magnetic powder in a glove box with an inert atmosphere protection, dry it naturally at room temperature, and finally obtain dry metal magnetic powder after chemical oxidation treatment.
[0042] Step 3, placing the chemically oxidized samarium iron nitrogen magnetic powder in an oxygen partial pressure furnace for heat treatment: placing the samarium iron nitrogen magnetic powder treated with phosphating and chemical oxidation in an oxygen partial pressure tube furnace, respectively, introducing a mixed gas of nitrogen and air or pure oxygen, and controlling the flow of air or pure oxygen so that the oxygen content in the furnace is 1-15 vol.%. The oxygen partial pressure furnace controls the temperature at 150-250°C, the heating and cooling rates are 2°C / min, and the holding time is 30min-2h. The samarium iron nitrogen magnetic powder with multiple synergistic protective films is taken out from the oxygen partial pressure tube furnace and collected, and the powder particles are observed for microscopic morphology.
[0043] Set up control groups 1, 2, 3, and 4, where: Control group 1 only had steps 1 and 2 in Example 1, but no step 3; Control group 2 only had steps 1 and 3 in Example 1, but no step 2; Control group 3 only had steps 2 and 3 in Example 1, but no step 1; The control group 4 was the samarium iron nitrogen raw powder without any treatment.
[0044] Figure 2 The transmission electron microscope (TEM) and EDS spectrum analysis results of the single SmFeN powder of Example 1 and Control Group 1 are shown. It can be seen from the experimental results that a uniform and dense phosphating film and a multiple synergistic protective layer of metal oxide film are formed on the surface of the powder particles after multiple synergistic surface treatment. However, the O element content on the outside of the magnetic powder of Control Group 1, which lacks step 3, is significantly less than that of Example 1 due to the lack of heat treatment process, which indicates that the oxide film on the outside of the magnetic powder is not dense enough, which will reduce the high-temperature oxidation resistance of the magnetic powder.
[0045] Weigh 3.5g-4.5g of the samarium iron nitrogen powders with different synergistic surface treatments collected in the above Example 1 and control groups 1-3 and the untreated samarium iron nitrogen original powders of control group 4, place the samarium iron nitrogen powders in a crucible, and place the crucible in a high-temperature heat loss test box for heat treatment at 200°C, 250°C and 300°C for 30 minutes respectively. The heat-treated powders are weighed on a high-precision electronic balance, the oxidation weight gain rate of the samarium iron nitrogen powders is calculated, the oxidation weight gain experiment of the samarium iron nitrogen powders is completed, and the antioxidant properties of the samarium iron nitrogen powders at various temperatures are analyzed. The data corresponding to the oxidation weight gain experiment are shown in Table 1.
[0046] The results of the oxidation weight gain experiment at different temperatures in Example 1 show that at 200°C, the samarium iron nitrogen powder with multiple synergistic surface treatments in Example 1 hardly exhibits oxidation behavior, and its oxidation resistance is significantly enhanced. As the temperature increases to 250°C and 300°C, the weight gain rate increases with temperature, but the increase is not large.
[0047] However, the control groups 1, 2, and 3 all had a higher weight gain rate than Example 1 at high temperature due to the lack of one of the steps, and the antioxidative performance of the samarium iron nitrogen powder at 200°C was similar to that of Example 1, and the increase was not very obvious. However, as the temperature increased to 250°C and 300°C, the weight gain rate was significantly increased compared with Example 1, indicating that the antioxidative performance of the powder was weakened compared with Example 1. The antioxidative performance of the powder in the control group 3 without step 1 was significantly weakened.
[0048] The results of the oxidation weight gain experiment at different temperatures for the control group 4 show that at 200°C, 250°C and 300°C, the samarium iron nitrogen powder is severely oxidized. Compared with Example 1, after multiple synergistic surface treatments in Example 1, a uniform and dense protective film is formed on the surface of the samarium iron nitrogen powder, which significantly enhances the high-temperature oxidation resistance of the samarium iron nitrogen powder at 200°C-300°C.
[0049] The SmFeN powders with multiple synergistic surface treatments collected in the above-mentioned Example 1 and Control Groups 1-3 and the untreated SmFeN raw powders in Control Group 4 were placed in a crucible, and the crucible was placed in a high-temperature heat loss test chamber for heat treatment at 200°C, 250°C and 300°C for 30 minutes. Weigh 3g of SmFeN powder, weigh 0.18g of paraffin wax according to the mass ratio of powder to paraffin wax 3:0.18, then grind and mix the weighed powder and paraffin wax in a mortar, and then use a manual hydraulic molding machine to cold-press the powder in the mold into a cylindrical block, the cold pressing pressure is 40KN, and the cold pressing time is 3min. Finally, the demolded block is tested for permanent magnetic properties using an automatic permanent magnetic property measuring instrument (AMT-4), and the corresponding data of magnetic properties are shown in Table 2.
[0050] The results of the permanent magnetic property test of Example 1 and Control Groups 1-4 using an automatic permanent magnetic property measuring instrument (AMT-4) show that the coercivity of the SmFeN powder is basically consistent with the antioxidant performance. The stronger the high-temperature antioxidant performance, the smaller the coercivity loss at high temperature.
[0051] Table 1 Comparison of the antioxidant properties of the powders obtained in different embodiments Sample name 200℃ΔW oxidation weight gain rate 250℃ΔW oxidation weight gain rate 300℃ΔW oxidation weight gain rate Example 1 0.0002 0.0057 0.0281 Control group 1 0.0009 0.0121 0.0596 Control group 2 0.0004 0.0096 0.0371 Control group 3 0.0011 0.0154 0.0632 Control group 4 0.2294 0.5303 0.9370 Table 2 Comparison of permanent magnetic properties of powders obtained in different embodiments Sample name Normal temperature Hcj / KOe 200℃Hcj / KOe 250℃Hcj / KOe 300℃Hcj / KOe Example 1 9.598 9.687 7.587 3.361 Control group 1 9.687 9.34 7.096 3.005 Control group 2 9.587 9.596 7.476 3.295 Control group 3 9.456 9.496 7.106 3.132 Control group 4 9.246 0.39487 0.15774 0.09774 As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a metal magnetic powder having multiple synergistic protective films on the surface, characterized in that: The method comprises: Under the protection of an inert atmosphere, the metal magnetic powder is placed in an organic solution containing concentrated phosphoric acid and stirred to obtain a surface-phosphorized metal magnetic powder; Under the protection of an inert atmosphere, the metal magnetic powder with phosphating on the surface is placed in an alkaline solution containing an oxidant, fully stirred at 25-80°C, and allowed to stand for reaction to obtain the metal magnetic powder after chemical oxidation treatment; Under the protection of an inert atmosphere, the metal magnetic powder after chemical oxidation treatment is cleaned and dried to obtain dry metal magnetic powder after oxidation treatment; The dried oxidized metal magnetic powder is placed in an oxygen partial pressure furnace for heat treatment, so that a layer of uniform and dense multi-layer protective film that is well bonded with the matrix is formed on the surface of the metal magnetic powder.
2. The method according to claim 1, characterized in that: The metal magnetic powder includes one of samarium iron nitrogen magnetic powder, neodymium iron boron magnetic powder, neodymium iron nitrogen magnetic powder, samarium cobalt magnetic powder, samarium iron cobalt magnetic powder and iron nitrogen compound magnetic powder or a composite thereof.
3. The method according to claim 1, characterized in that: The oxidant includes one of sodium nitrate, sodium nitrite, hydrogen peroxide, potassium dichromate and potassium permanganate.
4. The method according to claim 1, characterized in that: The solute in the organic solution containing concentrated phosphoric acid is concentrated phosphoric acid with a mass content greater than 80%, and the solvent is alkyl alcohol.
5. The method according to claim 1, characterized in that: The inert atmosphere includes one or both of argon and helium.
6. The method according to claim 1, characterized in that: The phosphoric acid content in the organic solution containing concentrated phosphoric acid is 0.5%-10% of the mass content of the magnetic powder.
7. The method according to claim 1, characterized in that: The oxidant content in the alkaline solution containing the oxidant is 0.1%-1.0% of the mass content of the magnetic powder.
8. The method according to claim 1, characterized in that: A mixed gas of nitrogen and air or a mixed gas of nitrogen and pure oxygen is introduced into the oxygen partial pressure furnace, and the flow rate of air or pure oxygen is controlled so that the oxygen content in the furnace is 1-15 vol.%.
9. The method according to claim 1, characterized in that: The oxygen partial pressure furnace controls the temperature at 150-250° C., the heating and cooling rates at 2-4° C. / min, and the heat preservation time at 30 min-2 h.
10. A metal magnetic powder having multiple synergistic protective films on its surface, prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Metal powder modifying liquid, modified metal powder, and preparation method of modified metal powder, and metal micro-powder based coating
CN106424701A
Preparation method for improving direct current superposition characteristic and frequency stability of iron-silicon-chromium magnetic powder core
CN106910614A
Rare earth bonded magnetic powder, preparation method thereof and bonded magnet
CN109841367A
Double-layer inorganic insulation coated soft magnetic powder and preparation method thereof
CN109979701A
Composite soft magnetic material and preparation method thereof
CN111540558A